Inter- and intra-species variation in genome-wide gene expression of Drosophila in response to parasitoid wasp attack - Salazar-Jaramillo, Laura (BMC Genomics, 2017)
BACKGROUND: Parasitoid resistance in Drosophila varies considerably, among and within species. An immune response, lamellocyte-mediated encapsulation, evolved in a subclade of Drosophila and was subsequently lost in at least one species within this subclade. While the mechanisms of resistance are fairly well documented in D. melanogaster, much less is known for closely related species. Here, we studied the inter- and intra-species variation in gene expression after parasitoid attack in Drosophila. We used RNA-seq after parasitization of four closely related Drosophila species of the melanogaster subgroup and replicated lines of D. melanogaster experimentally selected for increased resistance to gain insights into short- and long-term evolutionary changes. RESULTS: We found a core set of genes that are consistently up-regulated after parasitoid attack in the species and lines tested, regardless of their level of resistance. Another set of genes showed no up-regulation or expression in D. sechellia, the species unable to raise an immune response against parasitoids. This set consists largely of genes that are lineage-restricted to the melanogaster subgroup. Artificially selected lines did not show significant differences in gene expression with respect to non-selected lines in their responses to parasitoid attack, but several genes showed differential exon usage. CONCLUSIONS: We showed substantial similarities, but also notable differences, in the transcriptional responses to parasitoid attack among four closely related Drosophila species. In contrast, within D. melanogaster, the responses were remarkably similar. We confirmed that in the short-term, selection does not act on a pre-activation of the immune response. Instead it may target alternative mechanisms such as differential exon usage. In the long-term, we found support for the hypothesis that the ability to immunologically resist parasitoid attack is contingent on new genes that are restricted to the melanogaster subgroup. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-017-3697-3) contains supplementary material, which is available to authorized users.